What psychiatrists should know about environmental sustainability and what they should be doing about it. Issue 2 (May 2014) - Maughan, Daniel; Berry, Helen; Davison, Phil
Abstract : The 2013 report from the Intergovernmental Panel on Climate Change has caused renewed concern among both clinicians and health policy makers. Climate change is continuing at an increasing rate. This guest editorial describes how climate change might affect global mental health and proposes three things that psychiatrists from every country could implement to respond appropriately to this urgent and severe global threat. These responses are mitigation and adaptation strategies for mental health services, and the integration of sustainability into training.